ANALISIS FAKTOR-FAKTOR FUNDAMENTAL PERUSAHAAN PENGARUHNYA TERHADAP HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN DI BURSA EFEK INDONESIA - Rudianto, Dudi (Business and Management Review, 2010)
Fundamental analysis is carried out through review of financial ratios of companies is one important factor influence on stock prices. This study aims to analyze and know the effect of variable Return On Assets (ROA), Return On Equity (ROE), Book Value (BV), Debt Equity Ratio (DER) and Beta to the stock price at the mining company in Indonesia Stock Exchange (IDX) . From this research showed that the ROA has the highest sensitivity level of influence on stock prices, so any change in the level of ROA mining companies need to be carefully anticipated by each investor.   Keywords: ROA, ROE, BV, DER, Beta and  Stock  Price